Platelet Estimation by Manual and Automated Methods - M, Lavanya; C, Jayanthi; Alexandria, Maria; V, Janani (Annals of Pathology and Laboratory Medicine, 2019)
Background: Accurate platelet estimation is essential for the management of the patients with thrombocytopenia. Automated analyzer by its quick and reliable platelet estimation has overtaken the manual methods. But sometimes do produce erroneous results which are to be cross checked by manual methods. Hence this study was undertaken to compare the traditional manual method and alternate method based on Platelet/RBC ratio for estimating platelets in peripheral smear and to find the most accurate method for detecting Thrombocytopenia. Methods: 100 samples of EDTA anticoagulated blood is analysed by automated analyzer, then thin peripheral smear is prepared. Manual counts are performed by 1: Traditional Method- average platelet count / 10 Oil immersion field (OIF) x 15,000, 2: Alternate method -platelet/1000 red blood cells (RBC) multiplied by RBC count. Manual methods were compared with the automated analyzer using students t test. The Sensitivity, Specificity, Positive Predictive Value (PPV), Negative Predictive Value (NPV) and Likelihood ratio (LR) for positive tests were also calculated for the manual and alternate methods in detecting thrombocytopenia. Result: The students t test shows no difference in the platelet counts estimated by traditional method and alternate method. Further the results of sensitivity, specificity, PPV, NPV and LR for positive tests show the traditional and Alternate method can give fairly accurate results. Conclusion: The manual method of platelet estimation is found to be the most accurate and can used to quality check the automated analyzer or can be used in underprivileged laboratories, for aiding in proper management of the patient.